PENAFSIRAN SURAH AL KAUSAR DALAM PERSPEKTIF IMAM MAZHAB - Hasbi, Husnaini (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2024)
The interpretation of Surah Al-Kausar, which is the shortest letter in the Qur'an, has a variety of rich perspectives in the Islamic exegetical tradition. This article discusses the interpretation of Surah Al-Kausar from the perspective of four major school imams: Imam Abu Hanifah, Imam Malik, Imam Syafi'i, and Imam Ahmad bin Hanbal. Each imam gives a different interpretation of the meaning and message contained in this letter, based on the ushul fiqh methodology they adhere to. Imam Abu Hanifah tends to emphasize the social and economic aspects implied in this letter, especially in relation to the command to make sacrifices and pay attention to the poor. Imam Malik, with a focus on charity and worship, interprets Surah Al-Kausar as an encouragement to increase piety through sincere and continuous worship. Meanwhile, Imam Syafi'i provides a more legalistic interpretation, emphasizing the importance of fulfilling the requirements for carrying out worship as a form of obedience to Allah SWT. On the other hand, Imam Ahmad bin Hanbal sees Surah Al-Kausar as a symbol of Allah's gift of abundant blessings to the Messenger of Allah, who must be grateful for by increasing the quality of worship and devotion. This study provides in-depth insight into how different methodologies in fiqh science can produce diverse interpretations but still enrich Muslims' understanding of this letter. It is hoped that the results of this research can be a reference for academics and practitioners in understanding and practicing the teachings of the Qur'an more comprehensively.